A Study of Enhancing Training Effectiveness ‎PersonalizedEmployee-Development through ‎Generative AI (West Region Mid-Management IT ‎Employees-India)‎ - Khot, Anish (International Journal of Accounting and Economics Studies, 2025)
This paper develops a theoretical framework for understanding ‎the economic implications of AI-driven personalized training ‎systems in India’s information technology sector. Drawing ‎from human capital theory, technological research, and ‎organizational economics, we propose that AI-enhanced training ‎can address the fundamental challenges ‎facing IT workforce development. The framework synthesizes ‎existing economic theories with emerging research on AI-human ‎collaboration to identify key variables, propose testable ‎hypotheses, and outline implementation considerations for ‎Indian IT organizations. While empirical validation remains ‎necessary, this theoretical synthesis provides a foundation for ‎understanding how AI training systems might transform ‎workforce development economics in developing economic ‎contexts‎.